Does central coherence relate to the cognitive performance of children with autism in dynamic assessments?. (March 2013) - Aljunied, Mariam; Frederickson, Norah
Central coherence refers to an in-built propensity to form meaningful links over a wide range of stimuli and to generalize over as wide a range of contexts as possible. In children with autism this ability is diminished, and the impact of central coherence deficits in children with autism have previously been observed using static measures of learning, such as reading comprehension test performance. In this study, the relationship between central coherence and more dynamic indicators of learning are investigated. The responses of 52 children with autism (mean age 9:10 years) on a test of central coherence and a dynamic assessment task were analysed. All the children showed significant improvements in dynamic assessment test scores after mediation; however, among those with below average nonverbal intelligence scores, weak central coherence was significantly associated with smaller gains in performance after teaching. Implications for the validity of dynamic assessments for children with autism are discussed.